Simultaneous resection of a neuroendocrine tumor in an incidental Meckel’s diverticulum with transabdominal preperitoneal hernial repair: a case report - Shoko Kato; Takuya Saito; Shintaro Kurahashi; Yasuyuki Fukami; Shunichiro Komatsu; Kenitiro Kaneko; Tsuyoshi Sano (Surgical Case Reports)
Abstract Background As laparoscopic surgery becomes more prevalent worldwide, Meckel’s diverticula are increasingly being discovered incidentally during surgery. There is no consensus on whether to follow up or resect such diverticula, which are usually asymptomatic. In cases of transabdominal preperitoneal inguinal hernia repair, resection of such a diverticulum might add the risk of mesh infection. Thus, it is unclear whether simultaneous intestinal resection is advisable. Case presentation A 64-year-old man diagnosed with a left indirect inguinal hernia underwent laparoscopic inguinal hernia repair, during which a 2-cm Meckel’s diverticulum located contralateral to the mesentery of the ileum approximately 30 cm from Bauhin’s valve was detected incidentally. Because of the potential risk of future complications such as hemorrhage, diverticulitis, or tumor development, wedge resection of the ileum was performed extracorporeally through an extended umbilical port site after completion of the hernia repair. Pathological examination revealed a neuroendocrine tumor (G1) in Meckel’s diverticulum, which was successfully resected without any mesh infection or postoperative complications. Discussion Our patient’s clinical course raises two important issues. First, a Meckel’s diverticulum detected incidentally during laparoscopic surgery should be resected promptly because malignant tumors within such diverticula have frequently been reported. Second, simultaneous resection with hernia repair using mesh seems to be as safe as other clean-contaminated surgery. Conclusions Management of incidental Meckel’s diverticula should be selected by appropriate assessment for the risk of malignancy and complications.